Strategi Pemerintah Kampung dalam meningkatkan perekonomian masyarakat melalui pengembangan ekowisata mangrove Kampung Teluk Dore Kecamatan Makbon Kabupaten Sorong: The village government's strategy in improving the community's economy through the development of mangrove ecotourism Teluk Dore Village, Makbon Sub-District, Sorong Regency - Salmawati Salmawati; Awal Fikri; Masni Banggu (JOURNAL OF GOVERNMENT SCIENCE, 2022)
This study aims at identifying the efforts and obstacles of the village government in promoting mangrove ecotourism in Teluk Dore village. This research uses a descriptive qualitative approach. The findings shows that the efforts of the village government in promoting mangrove ecotourism are carried out by extending market-share through promotion in social media and the establishment of gazebos for meeting places, performing tourist attractions, improving accessibilities, improving ecotourism services, and empowering the organizarions. Its main obstacles are the lack of funding sources and inadequate ecotourism facilities and security patrols. Although sub-district and district government support the efforts of Teluk Dore village government, the lack of cooperation with other parties contributes to the problems in developing mangrove ecotourism Teluk Dore at higher level.